The Impact of Non-Financial Data Reporting on Reduction of Value Gaps - Elmgasbi, Alladyn (Journal of Finance and Financial Law, 2020)
Differences in the perception of value have been for years a source of conflict between the management and investors. The reason for the divergence was seen in non-financial data. Although the issue of non-financial data reporting is a widely discussed, initially there were no guidelines determining how and what should be reported. In addition, publication of this data was only intended to build trust and create a positive image. This article analyzes the impact of reporting non-financial environmental data on the value of a company, which was assumed to be the market capitalization.